2022
DOI: 10.1101/2022.04.01.486733
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial threat assessment of bacteriophage infection is mediated by intracellular polyamine accumulation and Gac/Rsm signaling

Abstract: When eukaryotic cells are killed by pathogenic microorganisms, damage-associated and pathogen-associated signals are generated that alert other cells of nearby danger. Bacteria can detect the death of their kin; however, how bacteria make threat assessments of cellular injury is largely unexplored. Here we show that polyamines released by lysed bacteria serve as damage-associated molecules in Pseudomonas aeruginosa. In response to exogenous polyamines, Gac/Rsm and cyclic-di-GMP signaling is activated and intra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…61 Recent work demonstrated that polyamines inhibit phage replication and once released from lysed infected cells serve as signalling molecules to activate phage defence in neighbouring uninfected cells through the Gac/Rsm pathway. 62 Again, it might be expected that phage-encoded SAMases would reduce the synthesis of polyamines and thus either protect the phage from direct inhibition or prevent the activation of host defences.…”
Section: Discussionmentioning
confidence: 99%
“…61 Recent work demonstrated that polyamines inhibit phage replication and once released from lysed infected cells serve as signalling molecules to activate phage defence in neighbouring uninfected cells through the Gac/Rsm pathway. 62 Again, it might be expected that phage-encoded SAMases would reduce the synthesis of polyamines and thus either protect the phage from direct inhibition or prevent the activation of host defences.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria have abundant strategies to resist phage infection (Hampton et al 2020), including the capability to activate defenses when they detect infections in nearby neighbors (de Mattos et al 2022), as well as complex abilities to sense and physically navigate their environment (Keegstra et al 2022; Wadhwa and Berg 2022). Indeed, both eukaryotes and bacteria have been found to avoid parasite exposure (Bru et al 2019; Gibson and Amoroso 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria can also carry any number of cytoplasmic defenses that operate after a phage infects the cell. In fact, bacteria can even activate intracellular defenses in response to signals from phage-infected neighbors (Høyland-Kroghsbo et al 2013, 2017; Tan et al 2015; Patterson et al 2016; Baskerville et al 2018; de Mattos et al 2022). Moreover, recent advancements have revealed an enormous diversity of previously-undiscovered defense systems (Millman et al 2020, 2022), suggesting that many more bacterial responses to phages remain to be found.…”
Section: Introductionmentioning
confidence: 99%